DECENT WORK IN TIMES OF ECONOMIC CRISIS: THREATS AND LESSONS LEARNED - Petrylaitė, Daiva (Teisė, 2015)
The economic crisis that shook the world in 2008 has affected the social and economic status of many State’s and business subjects as well as separate persons. All countries that faced the economic downturn took various actions related to economic, legal and social measures, which aimed to promote labour market and reduce the negative effects of the crisis. All these measures in one way or another determined the social, economic and legal situation of employees, especially of unemployed persons.This article aims to analyse and evaluate the consequences of legal decisions made during the economic crisis and threats caused by them in the context of the right to decent work. It starts by defining the concept of decent work as well as its peculiarities of legal regulation in the context of international labour law and doctrine. This is followed by the analysis of measures, related to employment rights, which were taken to tackle causes of the economic downturn in Lithuania, and their legal doctrinal assessment.The economic crisis that shook European and world markets in 2008 at once revealed threats to the social and economic safety of employees. The international community responded immediately to the situation by calling countries to take anti-crisis measures, in a way that the principle of decent work will be led and the minimum of fundamental labour and social rights that are in content with such principle will be ensured.In order to tackle causes of the economic crisis as well as trying to prevent even greater its impact, during the period of 2008–2012 the Lithuanian government took many measures to liberalise employment relations. However, no crucial and radical decisions were made, so labour market took the so-called self-regulation. In Lithuania during the crisis negative atmosphere both in moral and economic sense as well as the measures taken by employee and the position of the government, created preconditions to talk about fundamental labour right violations, therefore, it means the disregard of the principle of decent work.